A microsystem design for controlling a DC motor by pulse width modulation using MicroBlaze soft-core - Abdelkarim Zemmouri; Anass Barodi; Hamad Dahou; Mohammed Alareqi; Rachid Elgouri; Laamari Hlou; Mohammed Benbrahim (Institute of Advanced Engineering and Science, 2023)
This paper proposes a microsystem based on the field programmable gate arrays (FPGA) electronic board. The preliminary objective is to manipulate a programming language to achieve a control part capable of controlling the speed of electric actuators, such as direct current (DC) motors. The method proposed in this work is to control the speed of the DC motor by a purely embedded architecture within the FPGA in order to reduce the space occupied by the circuit to a minimum and to ensure the reliability of the system. The implementation of this system allows the embedded MicroBlaze processor to be installed side by side with its memory blocks provided by Xilinx very high-speed integrated circuit (VHSIC) hardware description language (VHDL), Embedded C. The control signal of digital pulse-width modulation pulses is generated by an embedded block managed by the same processor. This potential application is demonstrated by experimental simulation on the Vertix5 FPGA chip.